Article Retracted 22/07/2011 - GuST: Guaranteed Services Token Protocol for Real-Time Communications - Ozuomba, Simeon; Chukwudebe, Gloria A. (Journal of the Institute of Engineering, 2011)
This Article was RETRACTED on 22/07/2011 at the request of the authors because the paper has already been published in another journal in Nigeria. - Editor, JIE In this paper, Guaranteed Services Token (GuST) protocol for integrated services networks which can efficiently support diverse traffic consisting of hard and soft real-time traffic along with non-real-time traffic is proposed. This is to meet the increasing demand for better performance of real time communications required by distributed multimedia applications, process control, factory automation, etc. For some time now, timed-token protocols have become the preferred Medium Access Control (MAC) protocol for supporting modern real-time systems. However, the existing timed-token protocols have been studied, and inefficiencies discovered with the way asynchronous traffic is handled. GuST employs the timed-token mechanisms in the Timely-Token protocol along with that of Budget Sharing Token (BuST) protocol. We discussed some bounds on the behavior of GuST protocol. In particular, we show that the token is never late, and the transmission of asynchronous traffic is guaranteed. We also compared GuST protocol against the Timely-Token protocol and the BuST protocol. Our comparison focuses on the ability of those protocols to support synchronous and asynchronous traffic. We demonstrated that the performance achieved by GuST is better than Timely-Toke n and BuST protocols especially for a system with light load of real-time traffic but with heavy load of non-real-time traffic. GuST protocol can be incorporated into the Ethernet network to provide real-time performance guarantees to multimedia applications. It can also be used to improve on the throughput of the Profibus which is a Fieldbus network standard. Keywords: Timed-Token Protocol; Ethernet; Timely-Token Protocol; Budget Sharing Token Protocol; Integrated Services Networks; Real-Time Traffic; Non-Real-Time Traffic; Media Access Control (MAC); GuST: Guaranteed; Services Token protocol DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5112 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 197-210 Uploaded Date: 20 July, 2011